Skylark : a novel - McLain, Paula (Atria Books, 2026)
"1664. Alouette Voland is the daughter of a master dyer at the famed Gobelin Tapestry Works, who secretly dreams of escaping her circumstances and creating her own masterpiece. When her father is unjustly imprisoned, Alouette's efforts to save him lead to her own confinement in the notorious Salpãetriáere asylum, where thousands of women are held captive and cruelly treated. But within its grim walls, she discovers a small group of brave allies, and the possibility of a life bigger than she ever imagined. 1939. Kristof Larson is a medical student beginning his psychiatric residency in Paris, whose neighbors on the Rue de Gobelins are a Jewish family who have fled Poland. When Nazi forces descend on the city, Kristof becomes their only hope for survival, even as his work as a doctor is jeopardized"--